Influence of post-processing on the compressive behaviour of full-scale pultruded FRP columns: Holes and inserts. (1st September 2022) - Alajarmeh, Omar; Alhawamdeh, Mohammad; Shelley, Tristan; Mohammed, Ali; Nicol, Lachlan; Schubel, Peter; Zeng, Xuesen
Highlights: Drilling holes showed slight decrease in the axial load capacity, stiffness and toughness. Failure initiation and progression of FRP columns with winding fibre layers led by delamination. Wound-fibres prevented the spread of the interlaminar crack and facilitated progressive failure. Placing inserts in the PFRP columns contributed slightly to the axial load resistance and prevented local buckling failure. DIC technique and FE modelling showed the stress distribution on the PFRP columns with and without holes. Abstract: Pultruded Fibre Reinforced Polymer (PFRP) composite sections are being implemented extensively in many civil infrastructure applications due to their unique strength- and stiffness-to-weight ratio and non-corrosive nature. After production, PFRP sections are usually subjected to post-processing to enhance their versatility and structural integrity, including drilling holes and placing anti-crush inserts inside the hollow sections. This study investigates the influence of the drilled holes and the incorporated inserts on the compressive behaviour of PFRP sections. The effect of the quantity and diameter of the holes as well as the glued and unglued anti-crushed inserts inside the hollow part of the PFRP section was investigated experimentally. Finite element modelling was employed to simulate and validate the experimental behaviour of the PFRP columns under compressive loading. Digital Image Correlation (DIC) technique, using a high resolusion tracing camera, was utilised to capture the actual strain distribution at the outer surface of the PFRP sections to observe and correlate the impact of the holes and inserts with numerical solutions. Test results showed that the failure modes and load resistance capacity of PFRP columns were insensitive to the number of holes and the hole diameter due to the unique pull-winding manufacturing process, which results in continuous wound fibres around the perimeter. On the contrary, placing internal inserts prevented the occurrence of local buckling with slight enhancement in the axial load capacity. Moreover, delamination failure at the column corners was observed to occur prior to the local buckling and the final failure in the columns without and with inserts, respectively.